Implementasi E-Ujian Sebagai Sistem Penilaian Pembelajaran Daring di SMP Islam Roudlotus Saidiyyah Semarang - Hakim, M. Faris Al; Sugiharti, Endang; Alamsyah, Alamsyah; Arifudin, Riza; Abidin, Zaenal; Putra, Anggyi Trisnawan (Jurnal Abdi Negeri, 2024)
The presence of the COVID-19 outbreak has led to the implementation of online learning from the location of each home. SMP Islam Roudlotus Saidiyyah Semarang has transformed learning by utilizing various applications. However, for the purposes of final semester assessment or integrated assessment, an online exam application is needed that is easy to use and able to provide data on student learning outcomes accurately and quickly. The implementation method consists of preparation, training, and evaluation. The results of the training showed that the E-Ujian application as an application for online assessment has the potential to be applied at SMP Islam Roudlotus Saidiyyah Semarang. The utilization of the E-Ujian Application in learning activities in the partner environment is an effort to maintain the quality of learning.